(untitled) (Biological Sciences - PJSIR, 2021)
Moringa oleifera medicinal plant is used for medicinal purposes for the treatment of different types of human diseases. The fresh roots, stems, leaves, flowers and seeds have been selected for such medicinal purposes. The findings of present study indicated that an appreciable amount of proximate composition and phytochemical had been confirmed. The leaves and seeds for this study showed significant phytochemical sources including phenolic compound, flavonoid, tannin alkaloid and antioxidant content, whereas the most sensitive minerals composition sources including Ca, Fe, Mg, Na, K, antibacterial activity including the Escherichia coli, Bacillus cereus and Staphylococcus aurous were found to be the most sensitive, while Klebsiella pneumonia least sensitive in this study. The growth of Escherichia coli is mostly inhibited by all plants components. Whereas, flowers and leaves showed good inhibition zone against Escherichia coli. The flowers of Maringa oleifera possessed antibacterial protein and peptide which showed highly significant against Staphylococcus aurous, Escherichia coli, Klebsiella pneumonia, Pseudomonas, proteus and enterobacter. The research will be supported for nutrition and sources of new drugs for the treatment of the different types of diseases.